The Effect Of Organic Fertilizers On Plant Growth On The Amount Of Nutrients In The Soil (Eurasian Research Bulletin, 2024)
Today, organic fertilizers have a complex effect on the soil and have a positive effect on the growth, development and productivity of crops, including cotton. However, in order to increase their efficiency, organic fertilizers, including half-rotted cattle manure, should be studied individually in each soil-climate condition and agricultural crop. The main role in this is played by the state of soil fertility. The main substance determining soil fertility is humus. The higher the quantity and quality of humus, the higher the productivity. However, according to most scientists, the amount of humus in the soil has been significantly decreasing over the last 30-50 years. One of the main reasons for this process is the lack of organic fertilizers in agriculture.